Morphological-Nominal Norm and University Manuals of Morphology in Modern Eastern Armenian - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2021)
The manuals we have studied have a history of decades. During that time, the morphological norms of Eastern Armenian underwent certain changes, which, of course, could not be recorded in the mentioned textbooks. That is why there are some contradictions in the realities of the modern literary Armenian language used in the mentioned manuals. The article discusses the discrepancies that exist between the morphological-nominal norm of Modern Eastern Armenian and the rules presented in the aforementioned university manuals. The task is to consider them in the textbooks of this kind and other normative grammar textbooks from the point of view of the current norms of modern literary Eastern Armenian.